Doping charactristics of zinc oxide thin films deposited by thermal chemical vapour deposition : article - Rosley, Nor Syazwani; Ab. Kadir, Rosmalini (2010)
Nitrogen (N)-doped Zinc Oxide (ZnO) films were deposited on glass substrate by thermal chemical vapour deposition (CVD) process. Nitrogen gas with different flow rate was used as a dopant source. The effects of varying the carrier gas flow rate to the Zinc Oxide thin film electrical properties were investigated. In this experiment, it is found that NST N-doped ZnO thin film with 60 bubbles/min of nitrogen gas flow rate has optimum electrical properties with high conductivity. The types of metal contact used were gold-gold (Au-Au), gold-platinum (Au-Pt), gold-palladium (Au-Pd). AuAu contact with lowest resistivity obtained was observed as the best metal contact.